2015
DOI: 10.1053/j.gastro.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Lumen Imaging Probe Detects Esophageal Contractility Not Observed With Manometry in Patients With Achalasia

Abstract: Background & Aims The functional lumen imaging probe (FLIP) could improve characterization of achalasia subtypes by detecting non-occlusive esophageal contractions not observed with standard manometry. We aimed to evaluate for esophageal contractions during volumetric distention in patients with achalasia using FLIP topography. Methods Fifty one treatment-naïve patients with achalasia, defined and sub-classified by high-resolution esophageal pressure topography, and 10 asymptomatic individuals (controls) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
179
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(189 citation statements)
references
References 26 publications
6
179
0
3
Order By: Relevance
“…In support of this hypothesis, post-myotomy peristalsis in the Roman et al study was usually characterized as weak with low DCI values 34 . Along the same lines, FLIP detected non-occluding or occluding contractions in 10 of 10 patients with type III achalasia, two-thirds of the 26 patients with type II achalasia tested and one-third of the 15 patients with type I achalasia 42 .…”
Section: Achalasia With Preserved Peristalsismentioning
confidence: 67%
“…In support of this hypothesis, post-myotomy peristalsis in the Roman et al study was usually characterized as weak with low DCI values 34 . Along the same lines, FLIP detected non-occluding or occluding contractions in 10 of 10 patients with type III achalasia, two-thirds of the 26 patients with type II achalasia tested and one-third of the 15 patients with type I achalasia 42 .…”
Section: Achalasia With Preserved Peristalsismentioning
confidence: 67%
“…The benefits of FLIP topography are the ability to define EGJ distensibility and function while simultaneously obtaining information regarding the contractile activity and distensibility of the esophageal body. This approach has been utilized to better characterize the motor activity in the body of the esophagus in achalasia subtypes where patients were categorized based on three distinct body patterns that consisted of repetitive antegrade contractions (RACs), repetitive retrograde contractions (RRCs) or absence of activity (Figure 2) 11, 12 .…”
Section: Methodology and Technical Aspectsmentioning
confidence: 99%
“…In a study performed by Carlson et al, esophageal body contractility including propagating contractions were observed in a proportion of patients with all subtypes of achalasia during catheter bag distension. Often, this contractility was of an abnormal pattern, including repetitive retrograde contractions that were never observed in controls [79]. The significance of these propagating contractions is yet to be seen, but further study is certainly warranted to determine if their presence carry pathophysiologic or prognostic implications.…”
Section: The Importance Of the Timed Barium Swallowmentioning
confidence: 99%